"Hear me!". (1st February 2021) - Chiakpo, Evelyne
I am respectfully submitting a narrative essay to this journal. As a faculty member at a residency program, I got interested in contributing this essay after my experience caring for a disabled patient. I presumed we tend to imperfectly decipher what our patients' needs are and my experience highlighted the need to be more sensitive and less dismissive to patients with disabilities. I started with the assumption that there were minimal teaching points to the house staff since this was an overt outpatient placement case. I was wrong and learnt much more than I expected. As faculty physicians, we tend to highlight pertinent clinical data to the learners and inadvertently gloss over vital nonclinical details that ultimately are as important. This patient was very succinct with her demands and understandably upset with our blatant conjectures with our daily mundane clinical rounds and consults. Taking time to listen to her, having a team meeting in her room and coordinating her care with nursing and medical colleagues was not only a learning experience but made me a better physician and teacher. She was the focus and her needs were met, not ours. I have no financial conflict of interest, and the patient was aware I intended to share my experience with my peers. I will appreciate any feedback and opportunity to learn and improve this narrative with expected revisions.